2013
DOI: 10.1002/mus.23719
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin modulates cortical maladaptation in post‐stroke spasticity

Abstract: Cortical excitability changes were demonstrated in UH, suggesting that the clinical benefits of botulinum toxin relate to modulation of abnormal central reorganization (maladaptive plasticity) in post-stroke spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
2
23
1
Order By: Relevance
“…[29][30][31][32][33][34] The threshold-tracking strategy used a target response of 0.2 mV (±20%) located in the middle of the established linear relationship between the logarithm of the MEP amplitude and the stimulus intensity. 25 As such, selecting a target that is located in the steepest portion of the stimulus-response (SR) curve, relatively large variations in the MEP amplitude translate to relatively small variations in stimulus intensity or threshold.…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…[29][30][31][32][33][34] The threshold-tracking strategy used a target response of 0.2 mV (±20%) located in the middle of the established linear relationship between the logarithm of the MEP amplitude and the stimulus intensity. 25 As such, selecting a target that is located in the steepest portion of the stimulus-response (SR) curve, relatively large variations in the MEP amplitude translate to relatively small variations in stimulus intensity or threshold.…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…In addition, reduction of SICI over the contralateral and ipsilateral (unaffected) motor cortex was previously reported in acute stroke and was associated with a greater severity of functional limb impairment (Huynh et al. ,b,c). Of further relevance, normalization of SICI was reported secondary to botulinum toxin therapy and correlated with improvement in limb spasticity, suggesting the importance of modulating maladaptive cortical plasticity as a therapeutic approach (Huynh et al.…”
Section: Discussionmentioning
confidence: 65%
“…Of further relevance, normalization of SICI was reported secondary to botulinum toxin therapy and correlated with improvement in limb spasticity, suggesting the importance of modulating maladaptive cortical plasticity as a therapeutic approach (Huynh et al. ,b,c). Consequently, rehabilitative and pharmacological strategies aimed at restoring the cortical processes involved in regulating complex hand tasks, particularly functional coupling of the descending corticomotoneuronal volleys may prove therapeutically useful in humans.…”
Section: Discussionmentioning
confidence: 99%
“…BoNT-A on activities related to muscle stretch reflexes, such as an effect on -motor neurons at the neuromuscular junction, a change in stimulation of Ia muscle spindles due to degeneration of -neurons, decreased co-contraction, and decreased Renshaw inhibition of the H reflex 18 . In addition, a study of stroke patients has demonstrated that short-interval intracortical inhibition in the unaffected cerebral hemisphere recovers to a normal level after BoNT-A injection, suggesting an effect on the central nervous system 19 .…”
Section: Discussionmentioning
confidence: 99%